Effects of Porosity of Dry and Saturated Sandstone on the Energy Dissipation of Stress Wave - Yexue Li; Jing Wang (Advances in Civil Engineering)
A SHPB experiment of porous sandstone was conducted to discuss the influencing principle of porosity on the energy dissipation of stress wave across dry and saturated porous sandstones. Changes in porosity before and after the SHPB experiment were analyzed by nuclear magnetic resonance. Results show that the number of wave peaks in the T2 spectrum before and after the impact test of sandstone is unchanged, but the wave peak value corresponding to small pores increases. This result indicates that the sandstone structure remains in the microcrack formation stage because the stress wave energy is adequate only for forming new microcracks but not for tearing pores and increasing pore diameter. Results further show that, at the same porosity, saturated sandstone consumes less energy than dry sandstone. With increased porosity, the energy dissipation of saturated sandstone decreases, whereas that of dry sandstone increases. This phenomenon can be explained based on three aspects. First, according to the fracture mechanics theory, the surface tension of water and Stefan effect significantly hinder crack expansion. Therefore, generating a new surface to dissipate stress wave energy of saturated sandstone is more difficult than that of dry sandstone under the same porosity. Second, during impact loading, saturated sandstone is in a nondrainage state, and its deformation can be viewed approximately as the sum of compressive deformation of sandstone and water. Water has smaller comprehensive deformation than sandstone. The deformation of saturated sandstone decreases with increased porosity, i.e., water content. Plastic deformation and the probability of new cracks decrease, so energy dissipation of saturated sandstone decreases. Third, with increased porosity, the dynamic strength of dry sandstone declines accordingly. Developing new cracks during loading to dissipate stress wave energy as surface energy is easy. Therefore, high porosity causes great energy dissipation.